Improving efficiency of multi-phase cascaded DC-DC boost converters in discontinuous conduction mode suitable for renewable energy application - Rizqiawan, Arwindra; Muzakki, Muhammad Farras; Furqani, Jihad (Institute of Advanced Engineering and Science, 2025)
This study presents an improvement on the efficiency of a proposed multiphase cascaded DC-DC boost converter by employing discontinuous conduction mode(DCM) for its operation. The proposed multiphase cascaded DC-DC boost converter is characterized by high voltage gain and low input current ripple. This converter consists of two stages and is designed to connect a photovoltaic (PV)system to a DC microgrid bus. First, the loss equations for the converter are analyzed, then discontinuous conduction mode is applied to the first stage of the proposed converter by adjusting the second stage output current value, which represents grid load fluctuations. Subsequently, the efficiency of the proposed converter will be evaluated. Further, comparison with two operation modes, continuous conduction mode (CCM) and boundary conduction mode (BCM), is provided. To verify the proposed analysis and calculation, experiments are conducted by implementing the circuitry in a lab-scale prototype. The results show that by implementing DCM operation, the proposed converter achieves the high est efficiency of 92.2% at an output power of 120 W, while other modes achieve lower efficiencies as in CCM with 90.17% at an output power of 215.5 W. In the proposed converter, the dominant source of losses is attributed to the inductor, accounting for approximately 62% of the total losses in DCM. The operation of DCMhas demonstrated a substantial reduction in switching losses, leading to a notable increase in efficiency.